A Pilot Study on the Feasibility of an Extended Suckling System for Pasture-Based Dairies - Sandra Liliana Ospina Rios; Caroline Lee; Sarah J. Andrewartha; Megan Verdon (Animals, 2023)
This study investigated cow-calf productivity in a 10-week, pasture-based, extended suckling system featuring part-time cow-calf contact and once-a-day milking. A total of 30 dairy cows and their calves were assigned to two treatments: (1) cow and calf managed in an extended suckling system; or (2) cow and calf separated at birth and managed as usual. Cow-calf pairs grazed together during the day and spent the night separated by fence-line contact. The dams were reunited with the calves after once-a-day milking every morning. The commercial treatment pairs were separated after birth, and cows were milked twice a day and managed within the farm herd. Commercial calves were reared and managed as per commercial Australian practices. Cow-calf dams yielded 9 L/cow/day less saleable milk (p < 0.001), and their milk had lower fat (p = 0.04) but a higher protein percentage (p < 0.001) than commercial cows during pre-weaning. However, milk yield and composition were comparable post-weaning. Dam-suckled calves gained weight faster and were therefore weaned 2 weeks earlier than commercial calves, which were offered 8 L/day milk. This study has demonstrated a novel system of extended cow-calf suckling that could be practical to implement in pasture-based dairies. The long-term effects and scalability of the extended suckling system described here require further validation.